NP-completeness of the Eulerian walk problem for a multiple graph - Alexander V. Smirnov (Моделирование и анализ информационных систем, 2024)
In this paper, we study undirected multiple graphs of any natural multiplicity $k>1$. There are edges of three types: ordinary edges, multiple edges and multi-edges. Each edge of the last two types is a union of $k$ linked edges, which connect 2 or $(k+1)$ vertices, correspondingly. The linked edges should be used simultaneously. If a vertex is incident to a multiple edge, it can be also incident to other multiple edges and it can be the common end of $k$ linked edges of some multi-edge. If a vertex is the common end of some multi-edge, it cannot be the common end of another multi-edge. We study the problem of finding the Eulerian walk (the cycle or the trail) in a multiple graph, which generalizes the classical problem for an ordinary graph. We prove that the recognition variant of the multiple eulerian walk problem is NP-complete. For this purpose we first prove NP-completeness of the auxiliary problem of recognising the covering trails with given endpoints in an ordinary graph.